FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN E-GOVERNMENT PADA PELAYANAN PUBLIK (STUDI KASUS KABUPATEN MADIUN) - Bhaskara, Julio Adi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
This study aims to determine the factors that influence the community in the use of e-Government in public services. The development of e-Government in Indonesia has been carried out for more than ten years, but the participation and index of e-Government development in Indonesia based on rankings in Southeast Asia is still low. So it is important in this study to test the independent hypothesis that was built to see the relationship between people's intentions to use e-Government. This research is the result of a questionnaire that has been given by the people of Madiun Regency. The number of research respondents as many as 99 respondents and processed using SmartPLS 3.0 Software. The results showed that of the five hypotheses tested, only two showed a positive relationship with public intentions to use e-Government services. The privacy security factor becomes one of the important roles in increasing public intention to use e-Government services. Meanwhile, trust in the government is a requirement for public participation to participate in the development of e-government services.